2022
DOI: 10.3390/ijerph19126990
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cyanobacteria Blooms in Artificial Water Bodies—An Effect of Environmental Conditions or the Result of Anthropogenic Change

Abstract: Algal blooms are an emerging problem. The massive development of phytoplankton is driven partly by the anthropogenic eutrophication of aquatic ecosystems and the expansion of toxic cyanobacteria in planktonic communities in temperate climate zones by the continual increase in global temperature. Cyanobacterial harmful algal blooms (CyanoHABs) not only disturb the ecological balance of the ecosystem, but they also prevent the use of waterbodies by humans. This study examines the cause of an unusual, persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…According to potential pollution sources, the lake was divided into five sampling zones, including profundal, inflow, channel fuel, and mooring zones. Generally, high total phytoplankton biomass ranged within 28–70 mg L −1 , typical for strong blooms which lasted throughout the whole growing season, similar to other small water bodies under strong pressure [ 8 , 24 , 25 , 53 , 54 ]. Such high biomass is characteristic of lakes with progressive eutrophication.…”
Section: Discussionmentioning
confidence: 75%
“…According to potential pollution sources, the lake was divided into five sampling zones, including profundal, inflow, channel fuel, and mooring zones. Generally, high total phytoplankton biomass ranged within 28–70 mg L −1 , typical for strong blooms which lasted throughout the whole growing season, similar to other small water bodies under strong pressure [ 8 , 24 , 25 , 53 , 54 ]. Such high biomass is characteristic of lakes with progressive eutrophication.…”
Section: Discussionmentioning
confidence: 75%
“…However, in this study, the influence of meteorological and hydrological factors was less than that of physiochemical factors ( Figure 5 ). Excessive nutrient enrichment in water bodies undoubtedly promotes the growth of harmful cyanobacteria ( Nowicka-Krawczyk et al., 2022 ). Throughout the study period, the density of Microcystis aeruginosa showed a stronger correlation with NH 4 -N ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although TP reduction is widely used as a primary strategy to mitigate the severity of harmful algal blooms ( Pick, 2016 ), cases have shown that TP decreases can be accompanied by increases in chlorophyll a concentrations, suggesting that other abiotic factors may also influence the observed trends ( Huang et al., 2020 ). The study by Nowicka-Krawczyk et al. (2022) showed that the composition of cyanobacterial blooms is strongly influenced by the nitrogen/phosphorus (N/P) ratio, with N/P explaining 13.3% of the variation and PO 4 -P explaining 10.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Jest to bardzo niepokojące, gdyż zmiany takie zachodzą na obszarze wododziałowym z wielką ilością naturalnych wypływów wód podziemnych, inicjalnych odcinków cieków i zbiorników małej retencji. Jednym z przejawów zanieczyszczenia, niosącego za sobą groźbę dalszych szkodliwych zmian w środowisku wodnym okolic Łodzi, są wysokie stężenia biogenów (Nowicka-Krawczyk i in. 2022).…”
Section: Wprowadzenieunclassified